Estudio de la composición química y actividad antioxidante del aceite esencial de Luma chequen (Moliná) A. Gray "arrayán" - Carhuapoma Y., Mario (2005)
Oxidative stress generates several inflammatory diseases with cell death and carcinogenesis. Luma chequen (Molina) A. Gray "arrayán" is a native specie with anti-inflammatory and antimicrobial virtues and corpse (post mortem tissue) preservative .With the goal of characterizing the chemical composition and determining antioxidant activity of essential oil of L. chequen, it was carried out the present work. The essential oil reports a (1.25 % v /p) performance, (+6 a -8) optical rotation, (0.9044 g/mL) density and a (1.470) refraction index. By means of CG-SM and NMR-13C it was elucidated the structures of 40 compounds at a 93,6 % of the whole sample, monoterpenic hydrocarbons (68.8 %), containing α-pinene (57.3 %) and β-pinene (6.2 %) oxygenated hydrocarbons (18.9%), emphasizing 1,8 cineol (7.5 %), linalool (3.7 %), and trans-verbenol (2.2 %), sesquiterpenes (3.0 %), with β-selinene (1.3%) and β-cariofilene oxide (0.9%), and a non terpenic fraction (3.0%), It was assayed 3 models of antioxidant activity, 1) resulted very near to vitamin C, gaining over of the DPPH radical in 63.5600% and the vitamin C in 69.7767%, it has and CL50 of 43.3571 μg/ml and the vitamin C of 36.4090 μ/mL. 2) the winning of hydroxyl radical at concentrations of 100,50, and 10 μg/ml, resulting in 67.2033 and 31.2767%, respectively, at a greater concentration of oil, there is a greater antioxidant capacity and 3) it lnhibits the formation of malondialdehyde-thiobarbituric acid complex in 0.117 μmols/ml an the vitamin C, 0.103 μmols/rnl, comparing with negative control that exhibits 0.540 μmols/mL; essential of results with minor antioxidant capacity in this model. The results suggest that the essential oH of L. chequen has antioxidant activity, due to structure of their chemical constituent.